2014
DOI: 10.1155/2014/465173
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Maxillary Rhinosinusitis of Dental Origin: A Systematic Review of 674 Patient Cases

Abstract: Objectives. The aim of this systematic review is to study the causes of odontogenic chronic maxillary rhinosinusitis (CMRS), the average age of the patients, the distribution by sex, and the teeth involved. Materials and Methods. We performed an EMBASE-, Cochrane-, and PubMed-based review of all of the described cases of odontogenic CMRS from January 1980 to January 2013. Issues of clinical relevance, such as the primary aetiology and the teeth involved, were evaluated for each case. Results. From the 190 iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
82
1
16

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 93 publications
(112 citation statements)
references
References 42 publications
2
82
1
16
Order By: Relevance
“…Various odontogenic pathologies can cause ODS, including pulpitis, periapical lesions (cysts, abscesses, granulomas), periodontitis, oroantral fistula (OAF), or dental treatment‐related sinus foreign bodies . Large series and meta‐analyses have shown that the main dental etiologies of ODS are extraction‐related OAFs, periapical, and periodontal disease …”
Section: Introductionmentioning
confidence: 99%
“…Various odontogenic pathologies can cause ODS, including pulpitis, periapical lesions (cysts, abscesses, granulomas), periodontitis, oroantral fistula (OAF), or dental treatment‐related sinus foreign bodies . Large series and meta‐analyses have shown that the main dental etiologies of ODS are extraction‐related OAFs, periapical, and periodontal disease …”
Section: Introductionmentioning
confidence: 99%
“…19 Etiological meta-analysis developed by Arias-Irimia et al, performed on 770 patients with odontogenic paranasal sinusitis, described in 41 articles written between 1986 and 2007, showed that women constitute 57.7% of all patients suffering from odontogenic paranasal sinusitis. 20 55.97% of patients presented odontogenic changes of an iatrogenic profile.…”
Section: Discussionmentioning
confidence: 99%
“…Lechien et al 8 realizaram uma revisão sistemática sobre as causas da sinusite maxilar crônica odontogênica. Os resultados mostraram que 65,7% dos casos de sinusite odontogênica são de origem iatrogênica, já a presença de periodontite apical foi responsável por 16,8% dos casos.…”
Section: Alterações Dentárias E Sinusite Odontogênicaunclassified
“…7,8 Os sintomas dentários variam desde uma dor aguda associada à inflamação pulpar até a dor proveniente de uma infecção dentária envolvendo o osso ao redor, como a doença periodontal e periodontite apical. No entanto, por ser de origem odontogênica, geralmente, estes sintomas manifestam-se em apenas um lado da face, ao contrário da sinusite não odontogênica.…”
Section: Sintomasunclassified
See 1 more Smart Citation